The role of the Jadids in the reform of the national language and the formation of national identity - Farxodjonova, Nodira (The Lingua Spectrum, 2025)
At the end of the 19th and the beginning of the 20th century, the Jadid movement in Central Asia emerged not only as an educational and enlightenment campaign but also as a linguistic and cultural renaissance. This article analyzes the role of the Jadids in reforming the national language, transforming it into a means of public education and a tool for fostering national identity. In particular, the study examines the linguistic policies and ideas of prominent Jadid figures such as Mahmudkhoja Behbudi, Abdurauf Fitrat, Abdulla Avloni, and Munavvarqori Abdurashidkhonov concerning orthographic and grammatical reforms. Their concepts of “Writing in Turkic,” “Mother Tongue,” and “Language as the Soul of the Nation” are also explored.